The Effect of Individual Uncertainty on the Specificity of Human Capital: Empirical Evidence from Professional Soccer - Steffen Merkel; Sascha L. Schmidt; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2015)
This study uses the case of professional soccer to investigate the determinants of human capital (HC) specificity. Inspired by labor market research, we formulate three hypotheses on how uncertainty about the usefulness of individuals' (more productive) specific skills affects their investment in (more flexible) general skills. The empirical analysis is based on unique panel data on school grades, soccer evaluations, and the sociodemographic characteristics of 90 elite players from the youth academy of a German Bundesliga club. We find that senior and long-serving players, who are comparably certain that their (soccer) specific capital will be sufficient to ensure a lucrative professional contract, invest less in general HC at school. Expected soccer performance, in contrast, has a counterintuitive positive effect. Our results expand knowledge on the factors influencing HC specificity from the macro to the subject level and highlight practical implications for institutions that train gifted individuals.
Keywords: J24; I20; D81; D84; L83; 330; Individual uncertainty; human capital; skill specificity; professional soccer; youth academy